Are smallholder farmers credit constrained? evidence on demand and supply constraints of credit in Ethiopia and Tanzania - Balana, Bedru; Mekonnen, Dawit Kelemework; Haile, B.; Hagos, Fitsum; Yimam, S.; Ringler, Claudia (International Food Policy Research Institute, 2020)
Credit constraint is considered by many as one of the key barriers to adoption of modern agricultural technologies, such as chemical fertilizer, improved seeds, and irrigation technologies, among smallholders. Past research and much policy discourse associates agricultural credit constraints with supply-side factors, such as limited access to credit sources or high costs of borrowing. However, demand-side factors, such as risk-aversion and financial illiteracy among borrowers, as well as high transaction costs, can also play important roles in credit-rationing for smallholders. Using primary survey data from Ethiopia and Tanzania, this study examines the nature of credit constraints facing smallholders and the factors that affect credit constraints. In addition, we assess whether credit constraints are gender-differentiated. Results show that demand-side credit constraints are at least as important as supply-side factors in both countries. Women are more likely to be credit constrained (from both the supply and demand sides) than men. Based on these findings, we suggest that policies should focus on addressing both supply- and demand-side credit constraints, including through targeted interventions to reduce risk, such as crop insurance and gender-sensitive policies to improve women’s access to credit.